10 Years Prince Claus Fund 1996 - 2006 : 2006 Prince Claus Awards. - van der Plas, Els; Meta, Yovita; Sheriff, Abdul; Stagno, Bruno; van der Staay, Adriaan; Turner, Caroline; Duret, Marcel; Danticat, Edwidge; Kiendl, Anthony; The Prince Claus Fund, The Hague (The Hague : Prince Claus Fund, 2006)
Abdul, Lida ; Brodber, Erna ; Chakava, Herny ; Frankétienne ; Gauhar, Madeeha ; Kamandjâti, Al ; Mel, Michaele ; Tohme, Christine ; et al.
Overzicht 10 jaar Prince Claus Fund, The Hague
kunstcatalogus